2016
DOI: 10.1017/s0950268816001758
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant surgical site infections in a humanitarian surgery project

Abstract: The epidemiology of surgical site infections (SSIs) in surgical programmes in sub-Saharan Africa is inadequately described. We reviewed deep and organ-space SSIs occurring within a trauma project that had a high-quality microbiology partnership and active follow-up. Included patients underwent orthopaedic surgery in Teme Hospital (Port Harcourt, Nigeria) for trauma and subsequently developed a SSI requiring debridement and microbiological sampling. Data were collected from structured chart reviews and programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…In addition, a study done in Nigeria 19 found 32% MDR and staphylococcus aureus as the most common organism associated with SSIs. The reason for this variation in results could probably be due to differences in the antibiotic protocol being followed and hygienic measures in that particular hospital.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a study done in Nigeria 19 found 32% MDR and staphylococcus aureus as the most common organism associated with SSIs. The reason for this variation in results could probably be due to differences in the antibiotic protocol being followed and hygienic measures in that particular hospital.…”
Section: Resultsmentioning
confidence: 99%
“…In intensive care unit of a Nigerian hospital, out of 71 patients with healthcare-associated infection, bloodstream and urinary tract infections were the commonest infections, and S. aureus was the commonest cause of bloodstream infection with 80% of the S. aureus being MRSA [26]. In surgical site infections for 103 patients with orthopedic surgery in a hospital in Port Harcourt, Nigeria, the commonest pathogen was S. aureus (34%) including 15 patients with MRSA [27]. and prevalence of MRSA with mecA gene as 42.3% from 156 S. aureus in clinical isolates from South Western Nigeria with domination of SCCmec II and SCCmec V [28].…”
Section: Mrsa Prevalence In Africamentioning
confidence: 99%
“…Але перше місце в етіологічній структурі внутрішньолікарняних інфекцій посідають бактеріальні агенти: ентерококи, Streptococcus spp., Staphylococcus spp., Acinetobacter spp., Bacillus cereus, Legionella spp., представники родини Enterobacteriaceae (Proteus mirablis, Klebsiella pneumoniae, Escherichia coli, Serratia marcescens). Найголовніша роль у виникненні внутрішньолікарняних інфекцій, за даними всесвітньої статистики, належить Pseudomonas aeruginosa та Staphylococcus аureus (Abdallah et al, 2014;Khan et al, 2015;Murphy et al, 2016).…”
Section: ключові слова: антибіотики; дезінфектанти; біоплівки; Pseudounclassified
“…Моніторинг резистентності до антибактеріальних препаратів нозокоміальних штамів мікроорганізмівобов'язкова складова системи інфекційного контролю багатьох країн світу (Murphy et al, 2016;Choi et al, 2016;Iliyasu et al, 2016;Ramirez-Blanco et al, 2017;.…”
Section: обговоренняunclassified